Dynamic Characteristic Analysis of the Main Drive Gear Transmission System of a Large Shield Machine Considering Non-uniform Load Conditions - Deng Shuzhi; Xu Lixin; Long Bin; Su Cuixia (Jixie chuandong)
In order to investigate the dynamic characteristic of the parallel gear transmission system of the main drive of a large shield machine with multiple sources (including 16 sets of drive chains) under the load of non-uniform load condition, a bending-torsion coupled equivalent dynamics model of the main drive gear transmission system of a large shield machine with 230 degrees of freedom is established. In the modeling, the cutter torque and the overturning moment under the deflection load condition are calculated. The model analyzes the time-frequency dynamic response characteristics of the drive system under the action of the multi-source driving torque by considering the effects of nonlinear factors such as the time-varying meshing stiffness of gear teeth, gear transmission errors and backlash. The research results indicate that the vibration frequency components of the gear and the self-aligning bearings on both sides are mainly the gear meshing frequency, as well as the characteristic frequency of the bearing outer ring passing through. The maximum amplitude of the dynamic meshing force of the gear and the contact force of the bearing raceway occur at the corresponding meshing frequency and its harmonics, exhibiting obvious low-frequency vibration characteristics.Under non-uniform load conditions, there is a significant uneven load phenomenon in the meshing force between the small gears and the inner ring gear of the main drive group.